Covid-19 Fatalities and Internal Conflict: Does Government Economic Support Matter? - Mohammad Reza Farzanegan; Hassan F. Gholipour (Center for Economic Studies and ifo Institute (CESifo), 2021)
In this study, we look at the association between COVID-19 fatality rate and internal conflict, highlighting the importance of government economic support under the pandemic as a moderating factor. Our main hypothesis implies that increased COVID-19 fatality rates are likely to be positively associated with internal conflict in countries with lower levels of government economic support. Our empirical analysis confirms this prediction: employing cross-country data for more than 100 countries, the estimation results demonstrate that the positive effect of COVID-19 fatality rates on internal conflict may become insignificant with higher levels of government economic support. In countries where government spending in response to the pandemic is less than 5 to 6% of GDP, there is a significant risk of internal conflict resulting from increased COVID-19 fatality rates. Our main findings hold when we control for the effects of other socio-economic determinants relating to pre-pandemic internal political stability and alternative measures of conflict.
Keywords: D74; H51; H53; 330; Covid-19; conflict; political stability; fatality; fiscal measures